Markers of Inflammation and Fibrosis in the Orbital Fat/Connective Tissue of Patients with Graves' Orbitopathy: Clinical Implications. (16th September 2014) - Pawlowski, Przemyslaw; Reszec, Joanna; Eckstein, Anja; Johnson, Kristian; Grzybowski, Andrzej; Chyczewski, Lech; Mysliwiec, Janusz
Abstract : Purpose. To assess FGF-β, TGF-β, and COX2 expression and immunocompetent cells in the orbital tissue of patients with severe and mild Graves' orbitopathy. Patients and Methods. Orbital tissue was taken from 27 patients with GO: (1) severe GO (n = 18 ), the mean clinical activity score (CAS) being 8.5 (SD 2.5); and (2) mild GO (n = 9 ), the mean CAS being 2.2 (SD 0.8), and from 10 individuals undergoing blepharoplasty. The expression of CD4+, CD8+, CD20+, and CD68 and FGF-β, TGF-β, and COX2 in the orbital tissue was evaluated by immunohistochemical methods. Results. We demonstrated predominant CD4+ T cells in severe GO. CD68 expression was observed in the fibrous connective area of mild GO and was robust in severe GO, while the prominent TGF-β expression was seen in all GO. Increased FGF-β expression was observed in the fibroblasts and adipocytes of severe GO. No expression of COX2 was found in patients with GO. Conclusions. Macrophages and CD4 T lymphocytes are both engaged in the active/severe and long stage of inflammation in the orbital tissue. FGF-β and TGF-β expression may contribute to tissue remodeling, fibrosis, and perpetuation of inflammation in the orbital tissue of GO especially in severe GO.